Does Advertising Expenditure Impact Firm Value: A Case of Indian FMCG Industry (Global Journal of Management and Business Research, 2014)
This paper builds on the existing literature by studying the linkages between advertising expenditure, sales and profits in India. The paper takes a sample of 100 FMCG companies in India and studies their advertising and sales for the period ranging from 2001-02 to 2010-11.The study uses various tools including Mean, Standard Deviation, Coefficient of Variation, Kurtosis, Skewness, Correlation, Regression for getting insights into the data. Econometric analysis including Auto-correlation, Partial Auto-correlation, Augmented Dickey-Fuller test, Vector Auto Regression, Variance Decomposition Analysis, Johansen's Cointegration and Vector Error Correction Model have been employed to find out the bivariate relationship between the variables under reference. The paper points towards the dependency of sales revenue and profit after tax on advertising expenses besides showing an obvious impact of sales revenue on profits.
Keywords: FMCG; advertising expenditure; augmented dickey-fuller; vector auto regression; variance decomposition analysis; johansen#x2019; s cointegration; vector er